Evolution of Stative Participles in Pahari - Stroński, Krzysztof (Lingua Posnaniensis, 2014)
The point of departure for the present paper is the status of the bare participial form as inherited from MIA (Middle Indo-Aryan) by early NIA (New Indo-Aryan) with its stative force. It is a very well known phenomenon in the contemporary IA languages that the past participle can be extended by a past participle form based of the verb to be (e.g. MSH - Modern Standard Hindi - huā). It is also noticeable that not all NIA languages allow such extension and that several languages developed further, and reinterpreted the extended forms. The aim of the present paper will be to demonstrate how the stative participles developed in two branches of IA, namely Eastern and Western Pahari.1 The data for this preliminary research has been excerpted from Western Pahari inscriptions (Chhabra 1957), Eastern Pahari inscriptions (Pokharel 1974; Cauhān 2008; Joshi 2009), reference grammars and folk texts